1999
DOI: 10.1097/00005537-199906000-00027
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary function after total laryngectomy

Abstract: These results suggest that 42% of the laryngectomees tested may have benefited from further medical treatment. After laryngectomy, pulmonary function assessment was performed elsewhere in 1 of 59 cases. In light of the high prevalence of airway obstruction in laryngectomees, more frequent postoperative assessments of pulmonary function should be offered to prevent or to reduce impairment of respiratory function in this postlaryngectomy vulnerable pulmonary status. Further studies are also needed to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 12 publications
2
47
1
2
Order By: Relevance
“…The assessment of both quiet and deep breathing in the current study revealed a comparable pattern of respiratory kinematics in both participant groups. Although no previous studies have specifically examined kinematic measurements, research relating to general pulmonary function of laryngectomy patients postsurgery indicates a pattern of reduced vital capacity and expiratory flow postsurgery (Ackerstaff, Hilgers, Meeuwis, Knegt, & Weenink, 1999;Hess, Schwenk, Frank, & Loddenkemper, 1999). As spirometric measures were not conducted in the present study, the current authors are unable to confirm the presence or absence of any significant decline in lung capacity in the present group of participants.…”
Section: Discussioncontrasting
confidence: 62%
“…The assessment of both quiet and deep breathing in the current study revealed a comparable pattern of respiratory kinematics in both participant groups. Although no previous studies have specifically examined kinematic measurements, research relating to general pulmonary function of laryngectomy patients postsurgery indicates a pattern of reduced vital capacity and expiratory flow postsurgery (Ackerstaff, Hilgers, Meeuwis, Knegt, & Weenink, 1999;Hess, Schwenk, Frank, & Loddenkemper, 1999). As spirometric measures were not conducted in the present study, the current authors are unable to confirm the presence or absence of any significant decline in lung capacity in the present group of participants.…”
Section: Discussioncontrasting
confidence: 62%
“…Patients usually are accustomed to the changed ventilation process after a few months, and surgery‐associated factors such as pain, wound‐healing, and weakness are overcome. However, it is known that pulmonary function in these patients improves after tumor resection because the tumor previously has compressed the larynx . Most interestingly, in our study test results for MFEF 25–75 (L/s) and FEF 75 (L/s) decreased significantly after 3 months.…”
Section: Discussionmentioning
confidence: 46%
“…Aerodynamic force is a strong indicator of effort in voice generation, because the pulmonary condition of laryngectomees changes after removal of the larynx, thus altering the ability to control volume and respiratory frequency during speech, with a reduction of the ability to monitor airflow during speech, a greater use of pulmonary volumes associated with a greater ability of the pectoral wall, and the inability to produce long speeches. This may result in an increased effort to produce tracheoesophageal phonation . Among the laryngectomees studied here, pulmonary airflow was found to be probably maintained; it is possible that these patients could speak for long periods of time in social or professional situations, because there is maintenance of the expiratory airflow used during the production of tracheoesophageal voice.…”
Section: Discussionmentioning
confidence: 99%